Case report: a brain abscess in a disaster zone- beyond the call of duty. Issue 1 (December 2015) - Weiser, Giora; Mendlovic, Joseph; Dagan, David; Albukrek, Dov; Shpriz, Manor; Merin, Ofer
Abstract We present a case of a child with a suspected brain abscess treated by a military field hospital in post-typhoon Philippines. We review our intervention and decision process both at the field hospital and following his transfer to a referral center. These interventions were critical for his successful outcome.